Testing the limits of inclusive capitalism : a case study of the South Africa HP i-community - McFalls, Ricarda (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2007.